Effect of chlorine substituent on cytotoxic activities: Design and synthesis of systematically modified 2, 4-diphenyl-5H-indeno[1, 2-b]pyridines. Issue 7 (1st April 2016) - Kadayat, Tara Man; Park, Seojeong; Jun, Kyu-Yeon; Magar, Til Bahadur Thapa; Bist, Ganesh; Shrestha, Aarajana; Na, Younghwa; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: Abstract: In continuation of our previous work, six hydroxylated 2, 4-diphenyl-5 H -indeno[1, 2- b ]pyridine analogs were modified by introducing one chlorine functionality at ortho, meta or para position of the 2- or 4-phenyl ring. Eighteen new chlorinated compounds were thus prepared and assessed for topoisomerase inhibitory activity and cytotoxicity against HCT15, T47D, and HeLa cancer cell lines. All of the chlorinated compounds displayed significant cytotoxic effect, revealing potent anticancer activity against T47D breast cancer cells. This functional group modification allowed us to explore the importance of chlorine group substitution for the cytotoxic properties. The information reported here provides valuable insight for further study to develop new anticancer agents using related scaffolds.